The Association of Screen Time, Television in the Bedroom, and Obesity Among School‐Aged Youth: 2007 National Survey of Children's Health. (8th July 2013) - Wethington, Holly; Pan, Liping; Sherry, Bettylou
ABSTRACT: BACKGROUND: Among school‐aged youth, we sought to identify characteristics associated with (1) exceeding screen time recommendations (ie, television/videos/video games more than 2 hours/weekday), and (2) exceeding screen time recommendations, the presence of a television in the bedroom, and obesity. METHODS: Using 2007 National Survey of Children's Health data, we used multivariable logistic regression to identify sociodemographic and behavioral characteristics associated with excessive screen time among 6 to 11‐ and 12 to 17‐year‐olds on a typical weekday. For 12 to 17‐year‐olds only, we used logistic regression to examine the odds of obesity using the same variables as above, with the addition of screen time. RESULTS: Overall, 20.8% of 6 to 11‐year‐olds and 26.1% of 12 to 17‐year‐olds had excessive screen time. For both age groups, having a bedroom TV was significantly associated with excessive screen time. For the older age group, the dual scenario of excessive screen time with a bedroom TV had the strongest association with obesity (OR = 2.5, 95% CI 1.9, 3.2). CONCLUSIONS: Given the similar risk factors for excess screen time and having a TV in the bedroom, a public health challenge exists to design interventions to reduce screen time among school‐aged youth.